The therapeutic benefits of using medicinal plants in the treatment of Candidiasis: An analysis of the literature (Research, Society and Development, 2025)
Vaginal candidiasis is a common infection caused by the fungus Candida albicans, affecting many women, especially those of reproductive age. Despite the effectiveness of conventional treatments, prolonged use may lead to side effects and fungal resistance. Thus, there is growing interest in the use of medicinal plants, which contain natural compounds with antifungal action and may represent a safe and accessible alternative. Objective: To analyze the therapeutic benefits of medicinal plants in the treatment of vulvovaginal candidiasis. Methodology: This is an integrative literature review. Articles available in the Virtual Health Library (VHL) were selected, including the MEDLINE, LILACS, and BDENF databases. The descriptors used were: “Medicinal Plants,” “Nursing,” “Candidiasis,” “Plant Benefits,” and “Women’s Health.” The guiding question was: “What are the contributions of the use of medicinal plants in the treatment of women of reproductive age infected with Candida albicans?” Results: Five studies analyzed highlight the therapeutic potential of medicinal plants in combating Candida albicans. A reduction in vaginal candidiasis symptoms was observed, suggesting that these natural resources may serve as an effective complementary treatment. Conclusion: Medicinal plants show significant potential in the treatment of vulvovaginal candidiasis, especially considering the search for natural and accessible options compared to conventional antifungals. Species such as ginger, tea tree, and garlic demonstrated effectiveness, helping both in symptom relief and in reducing recurrences. Therefore, phytotherapy stands out as a complementary practice in women’s health care, valuing traditional knowledge alongside scientific evidence for a more humanized and efficient approach.